2010
DOI: 10.1128/jcm.00414-10
|View full text |Cite
|
Sign up to set email alerts
|

The Streptococcus milleri Population of a Cystic Fibrosis Clinic Reveals Patient Specificity and Intraspecies Diversity

Abstract: The genetic relatedness of Streptococcus milleri group isolates from the airways of cystic fibrosis patients was determined by using pulsed-field gel electrophoresis. This study reveals no evidence for patient-to-patient transmission in our patient population; however, within individual patients, complex inter-and intraspecies diversity and dynamics can be observed.In addition to their role in purulent infections (3,7,11), members of the Streptococcus milleri group (SMG), also known as the Streptococcus angino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…Resolution of the symptoms of clinical exacerbation was associated with antistreptococcal therapy and reduction in the density of this bacterium in sputum, suggesting that these bacteria may be a cause of pulmonary exacerbations in CF (544). Genotyping did not show evidence of patient-to-patient transmission, suggesting that patients are infected by their own endogenous flora (546). Other streptococci, such as S. agalactiae, have also been associated with CF.…”
Section: Other Microbesmentioning
confidence: 90%
“…Resolution of the symptoms of clinical exacerbation was associated with antistreptococcal therapy and reduction in the density of this bacterium in sputum, suggesting that these bacteria may be a cause of pulmonary exacerbations in CF (544). Genotyping did not show evidence of patient-to-patient transmission, suggesting that patients are infected by their own endogenous flora (546). Other streptococci, such as S. agalactiae, have also been associated with CF.…”
Section: Other Microbesmentioning
confidence: 90%
“…Furthermore, it was demonstrated that some of these same gene modulations could be mediated by the quorum-sensing molecule AI-2, which can accumulate to high levels in the sputum of CF patients, suggesting that intermicrobial communication between microbes of the "normal" flora may exacerbate CF disease caused by classical pathogens. A culture-independent analysis of a small cohort of CF patients revealed that SMG organisms not only were found during episodes of CF airway exacerbations but also were the numerically dominant species present (195). While the virulence mechanisms of SMG are unclear at this time, future studies should determine whether the increased infectious burden, the quorum-sensingenhanced virulence of other species present, or a combination of these effects results in enhanced CF disease.…”
Section: Infection Of the Cystic Fibrosis Lungmentioning
confidence: 99%
“…For example, it was demonstrated in experimental animals that the presence of avirulent, oropharyngeal flora significantly increased the pathogenicity of P. aeruginosa (345). Another example is the need for antibiotic therapy of the Streptococcus milleri group as a new pathogen in the CF lung in order to prevent a loss of lung function and reduce the frequency of exacerbations (367). The actual culture-based techniques to identify causative pathogens of CF lung disease are inadequate to identify microbial community richness.…”
Section: The Cf Microbiomementioning
confidence: 99%